An unusual case of fever and a sigmoid mass. (30th March 2011) - Kubba, Tamara; Takatsuka, Mio; Stern, Eve; Smith, Thomas; Lee, Jason; Al-Whouhayb, Maitham; Saunders, Michael
Abstract : A 52-year-old Afro-Caribbean female presented with a 2-week history of left iliac fossa pain and persistent fever. The working diagnosis was diverticulitis and she was treated with intravenous antibiotics. A CT scan of the abdomen showed a thickened sigmoid colon lying adjacent to the left bladder wall with inflammatory changes present. As the patient's condition showed no improvement, an explorative laparotomy was performed, which identified a mass in the sigmoid colon adherent to the bladder and left ovary. An anterior resection, partial cystectomy and a defunctioning loop-ileostomy were performed. Postoperatively, spiking fever with a high white cell count continued. No postoperative surgical complications were identified despite numerous investigations. Eventually, histology of the colon revealed a null type anaplastic large cell lymphoma with a high proliferation fraction of greater than 90%.